Dasar Wanita Negara: Daripada Polisi kepada Pelaksanaan - Ahmad, Noor Azizah; Abdul Ghani, Mariny (UUM Press, 2016)
The National Policy on Women is formulated to syncronize programmes and activities pertaining to the intergration of women in national developments. Implementation of such policy requires wholistic involvement from all stakeholders in order to perform to their respective roles effciently. The deeds are essential to ensure the objectives for women’s intergration in all sectors of national development as well as for promoting gender equality and women’s empowerment in Malaysia are achievable. Accordingly, a number of measures had been taken as well as on-going executions in conjunction with the strategies and approaches stated in The National Policy on Women (1989 and 2009) and also The Plan of Action for the Advancement of Women (1997 and 2009). This concept paper aims to discuss the women’s empowerment programmers and activities in particular to enhance awareness on the women’s rights as well as upgrading their knowledge and capabilities in economic activities through training along with financial supports programmed. Stakeholders such as the Ministry of Women, Family and Community Development, Department of Women’s Development, Department of Social Welfare, and non-governmental organizations play major roles in implementing these programmed.